Maternal and child health nursing : care of the childbearing and childrearing family - Pillitteri, Adele (Philadelphia, PA : Lippincott Williams & Wilkins, 2007)
Designed to help nurses understand wellness and illness as family-centered events, using a nursing process framework, this book presents the key terms, learning objectives, case studies, and critical thinking exercises
t t t
Includes bibliographical references and index
Keywords: Maternity nursing; Pediatric nursing; Maternal-Child Nursing; Family Health